Marsha : the Joy and Defiance of Marsha P. Johnson - Tourmaline (New York : Tiny Reparations Books, an imprint of Penguin Random House LLC, 2025)
"Black trans luminary Tourmaline brings to life the first definitive biography of the revolutionary activist Marsha P. Johnson, one of the most important and remarkable figures in LGBTQ+ history, revealing her story, her impact, and her legacy. This book will take readers into Marsha's childhood as she struggled with gender identity in the 1950s, to her dramatic and essential involvement in the Stonewall Riots and her activism for trans rights through the 70s to the AIDS crisis, and finally, it will explore her mysterious and still unresolved death."--
Includes bibliographical references and index.
Keywords: Johnson, Marsha P., -- 1945-1992.; Minority transgender women -- New York (State) -- New York -- Biography; Transgender people -- New York (State) -- New York -- Biography; Sexual minority activists -- New York (State) -- New York -- Biography; LGBT activism -- New York (State) -- New York; Stonewall Riots, New York, N.Y., 1969.; Gender minorities; LGBTQ+ activism; LGBTQ+ activists; LGBTQ+ people; LGBTQ+ riots; LGBTQ+ biographies; Transgender biographies